NORTRYPTYLINE ACT AS A POTENTIAL ADJUVANT TO DEXIBUPROFEN IN THE PREVENTION OF MIA INDUCED OSTEOARTHRITIS IN RAT MODEL OF CHRONIC PAIN AND PAIN INDUCED DEPRESSION. - V.S.SARAVANAN,; V.KRISHNARAJU, (International Journal of Pharma and Bio Sciences, 2013)
Osteoarthritis (OA) commonly known as wear and tear arthritis is more prevalent due to increasing aged population and obese people worldwide. OA is also associated with depression. Effective therapy regimen for the OA addressing both pain and depression is limited. Therefore, research on OA is need of the hour. Non-Steroidal anti-inflammatory drugs (NSAIDs) are the conventional OA treatment and TCAs has been extensively studied as adjuvant to enhance analgesic effect. As TCAs has shown analgesic effect and basically they are antidepressants, the synergistic effect of Nortryptyline (TCAs) with dexibuprofen (NSAID) and individual drugs has been evaluated in mono-sodium Iodo acetate (MIA) induced OA in rats for its analgesic and antidepressant effects. The results have shown that the combination of dexibuprofen and nortryptyline has synergistic analgesic effect and in addition relieved the chronic pain induced depression.